THE BRAZILIAN REACTIONS TO THE SNOWDEN AFFAIRS: IMPLICATIONS FOR THE STUDY OF INTERNATIONAL RELATIONS IN AN INTERCONNECTED WORLD - Thiago Borne Ferreira; Diego Rafael Canabarro (Revista Conjuntura Austral, 2015)
Despite of the central role the Internet plays in cyberspace-related matters, it was only when Edward Snowden brought light to American-led digital espionage programs that Internet governance and cybersecurity agendas definitely converged. The Snowden Affairs increased the entropy within the broader Internet ecosystem and reignited political tensions that revolve around the US prominence within the narrower arena of critical Internet resources management. In this context, many countries have shown great concern regarding the governance of the Internet, and Brazil has gained a prominent role in the debate. This paper (a) summarizes the concerns arisen from Snowden's leaks and their general impacts over the Internet governance ecosystem; (b) tracks the policy actions undertaken by Brazil in the issue-area of Internet governance both before and after Snowden; and (c) details how Brazil seized the Snowden Affair as an opportunity to promote its broader political agenda internationally, fostering a more democratic and pluralistic Internet governance worldwide. In the end, the paper reflects upon the prospects for change in global Internet governance after the US government announced its intention to relinquish its privileged position vis-a-vis critical Internet resources.